Effects of cholesterol-lowering probiotics on non-alcoholic fatty liver disease in FXR gene knockout mice - Yang, Minghua; Wang, Haoyang; Bukhari, Ihtisham; Zhao, Ye; Huang, Huang; Yu, Yong; Sun, Xiangdong; Mi, Yang; Mei, Lu; Zheng, Pengyuan (Frontiers in Nutrition, 2023)
Background/aims: Some studies showed that probiotics could improve the composition and structure of gut microbiota. Changes in the gut microbiota may alter bile acids (BAs) composition and kinetics, improving non-alcoholic fatty liver disease (NAFLD). However, it still needs to be clarified is still not clear that how probiotics improve both the metabolism of BAs and NAFLD. This work aimed to reveal the regulatory mechanisms of cholesterol-lowering (CL) probiotics on NAFLD from aspects involved in BA metabolism in FXR gene knockout (FXR -/-) mice. 2 Methods: FXR -/-male mice were randomly divided into three groups based on different interventions for 16 weeks, including normal diet (ND), high-fat diet (HFD) and probiotics intervention in HFD (HFD+P) group. 16s rDNA sequencing and Ultrahigh performance liquid chromatography tandem mass spectrometry (UHPLC-MS/MS) were utilized to analyze the changes in of gut microbiota and fecal bile acids in mice.Results: We found that the intervention of the CL-cholesterol-lowering probiotics improved liver lipid deposition and function in HFD-induced NAFLD mice by decreasing the levels of total cholesterol (TC) (p=0.002) and triglyceride (TG) (p=0.001) in serum, as well as suppressing liver inflammation, such as interleukin-1 beta (IL-1β) (p=0.002), tumor necrosis factor-alpha (TNF-α) (p<0.0001). 16S rDNA sequencing and metabonomic analyses showed that probiotics effectively reduced the abundance of harmful gut microbiota, such as Firmicutes (p=0.005), while concomitantly increasing the abundance of beneficial gut microbiota in NAFLD mice, such as Actinobacteriota (p=0.378), to improve NAFLD. Compared with the ND group, consuming an HFD elevated the levels of total BAs (p=0.0002), primary BAs (p=0.017), and secondary BAs (p=0.0001) in mice feces, while the intervention with probiotics significantly reduced the increase in the levels of fecal total bile acids (p=0.013) and secondary bile acids levels (p=0.017) induced by HFD.The CL-cholesterol-lowering probiotics were found to improve liver function, restore microbiota balance, correct an abnormal change in the composition and content of fecal bile acids, and repair the damaged intestinal mucosal barrier in 3 mice with NAFLD, ultimately ameliorating the condition. These results suggested that CL-cholesterol-lowering probiotics may be a promising and health-friendly treatment option for NAFLD.